Family Expectations on Hemodialysis Service Resilience in Disaster Situations: A Qualitative Study - Santi Setiawati; Dien Gusta Anggraini Nursal; Yessy Markolinda (Poltekkes Kemenkes Jakarta III, 2026)
Hemodialysis is a renal replacement therapy highly dependent on the availability of medical-grade water, stable electricity, and supporting technological systems. This dependency makes hemodialysis services vulnerable to disruption during disasters, particularly in earthquake- and flood-prone areas. Treatment interruption may increase the risk of serious complications and threaten patient safety. In this context, families play an essential role in maintaining therapy continuity; however, their perspectives in disaster mitigation remain underexplored. This study aimed to explore family expectations regarding the resilience of hemodialysis services in disaster situations. A qualitative exploratory approach with thematic analysis was employed. Primary informants consisted of two family members of hemodialysis patients, supported by source triangulation through interviews with one manager, one nurse, and two patients. Data were collected through in-depth interviews and analyzed using thematic analysis. The findings identified four main themes: (1) expectations for clear and structured hospital preparedness systems, (2) the need for technical education and risk communication, (3) clarity of emergency referral systems and alternative service networks, and (4) comprehensive protection of patient safety. The results indicate that families expect a structured mitigation system that is well-communicated and actively involves them in pre-disaster simulations and education. This study highlights that the resilience of hemodialysis services in disaster situations depends not only on infrastructure and hospital management but also on empowering families as integral components of the healthcare resilience system. Integrating families into preparedness planning may strengthen therapy continuity and enhance patients’ sense of security during crises.